2022
DOI: 10.34067/kid.0001442022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Iron Availability with Roxadustat in Nondialysis- and Dialysis-Dependent Patients with Anemia of CKD

Abstract: Background: Roxadustat, a hypoxia-inducible factor prolyl hydroxylase inhibitor, increases hemoglobin by stimulating erythropoietin synthesis, and improving iron availability through facilitation of iron uptake and/or release from stores. In this exploratory analysis, we assessed the effect of roxadustat treatment on laboratory parameters related to iron metabolism in patients with anemia of chronic kidney disease (CKD). Methods: Data were pooled from pivotal, randomized, phase 3 roxadustat trials: three plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 31 publications
(59 reference statements)
2
23
0
Order By: Relevance
“…This study also reported variable ferritin and serum iron results between the roxadustat 2.0‐ and 2.5‐mg/kg starting dose groups. Previous studies in patients with anemia of CKD have reported a reduction in ferritin and increase in serum iron when treated with roxadustat, 9,10,22,23 which is indicative of increased iron mobilization and utilization for erythropoiesis 24 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study also reported variable ferritin and serum iron results between the roxadustat 2.0‐ and 2.5‐mg/kg starting dose groups. Previous studies in patients with anemia of CKD have reported a reduction in ferritin and increase in serum iron when treated with roxadustat, 9,10,22,23 which is indicative of increased iron mobilization and utilization for erythropoiesis 24 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with anemia of CKD have reported a reduction in ferritin and increase in serum iron when treated with roxadustat, 9,10,22,23 which is indicative of increased iron mobilization and utilization for erythropoiesis. 24 In this population, most patients achieved Hb increases of ≥1, ≥1.5, and ≥2 g/dL at any point within the 16-week treatment period.…”
Section: Safetymentioning
confidence: 91%
See 2 more Smart Citations
“…Similar decreases in ferritin have been seen in earlier roxadustat studies, especially in patients with higher baseline ferritin. 24,[37][38][39] However, the DENALI study was not specifically designed to assess the impact on iron mobilization and utilization, which are both affected by multiple factors that were not systematically captured during this study.…”
Section: Discussionmentioning
confidence: 99%